Trade Union Channels for Influencing European Union Policies - Larsson, Bengt (Nordic Journal of Working Life Studies, 2015)
This paper analyzes what channels trade unions in Europe use when trying to influence European Union (EU) policies. It compares and contrasts trade unions in different industrial relations regimes with regard to the degree to which they cooperate with different actors to influence EU policies, while also touching on the importance of sector differences and organizational resources. The study is based on survey data collected in 2010–2011 from unions affiliated with the European Trade Union Confederation and from below peak unions in 14 European countries. Results of the survey show that the ‘national route’ is generally the most important for trade unions in influencing EU policies in the sense that this channel is, on average, used to the highest degree. In addition, the survey delineates some important differences between trade unions in different industrial relations regimes with regard to the balance between the national route and different access points in the ‘Brussels route’.